TOEI FRAMEWORK: ANALYSING TECHNOLOGY ADAPTATION FOR SUPPORTING MSME SUSTAINABILITY IN BALI - Putri, I Gusti Agung Prabandari Tri; Dwi Putri, I Gusti Agung Pramestri; Dewi, Desak Putu Nitya; Salilama, Fikri; Premana, I Made Sarwa (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The sustainability of MSMEs is one of the important issues for economic growth, because the existence of this business is more adaptive to change and has the opportunity for resilience in uncertainty. This study aims to analyze the sustainability of MSMEs based on their technological adaptation through social media by referring to the TOEI framework. Quantitative design is considered appropriate for the purpose of the study by utilizing a questionnaire as a data collection instrument targeting MSME owners in Bali Province. The sampling technique applied is probability sampling with the provisions of SEM analysis, the minimum sample size is 145 and the maximum is 290 data. Based on the results of data collection in the field, 190 valid data were obtained to enter the analysis stage. Data analysis was carried out using WarpPLS 7.0 software because the analysis is simpler. The results of the study indicate that the adoption of social media is positively and significantly influenced by technological factors, environmental factors and individual factors, while organizational factors do not show a significant influence. Regarding the sustainability of MSMEs, only organizational factors and social media adoption practices show a positive and significant influence. This study also proves that the adoption of social media can act as a mediator of the influence of technological factors and environmental factors on the sustainability of MSMEs. In the long term, the research results can be applied to MSMEs by improving the quality of social media so as to support MSMEs to be more adaptive, facilitate the determination of resilience strategies, improve performance, and mitigate risks.